Design of Fully Automated Depot Train Inspection Operation Management System Architecture Based on Digital Twin - Kai FENG; Hui ZHENG (Chengshi guidao jiaotong yanjiu, 2024)
[Objective] Digital twin technology is the booster for many industries to embark on the path of intelligence, information, and digitalization. To promote the digital development of urban rail transit vehicle bases, a fully automated depot train inspection operation management system based on digital twin is proposed, and the architecture design is explored. [Method] The conceptual architecture, technical architecture, storage layer architecture, and security architecture of the fully automated train inspection operation management system based on digital twin are introduced. [Result & Conclusion] The application of the system in the vehicle base of Nanning Metro Line 5 demonstrates that digital twin technology enables the monitoring of operational standards, operation quality traceability, production safety monitoring, and business statistical analysis at the vehicle base, which is conducive to the construction of an intelligent maintenance workshop that integrates ′safety, efficiency, and intelligence′.